The International and Political Journal: The intellectual and political foundations of the emergence of Israeli society - Ibrahim, Assistant Prof. Dr. Saad Hamid (The International and Political Journal, 2024)
In light of recent events and the developments witnessed by the Palestinian issue, it is imperative for us to study the Zionist society and know its formations and the foundations on which this society was created, The Zionist society was created in a very different way from other societies, as it consists of the diaspora of Jews present in the world, and this is what distinguishes it from other countries. Accordingly, this aims to study the emergence and formation of this society, as well as to study the foundations on which this society was founded , This is in three sections, the first is entitled The Nature of Israeli Society, the second is entitled The Social Structure in Israel, and the third is the intellectual foundations for the emergence of Israeli society. Keywords: intellectual foundations, political foundations, upbringing and formation, Israeli society.